2002
DOI: 10.1097/00002030-200204120-00016
|View full text |Cite
|
Sign up to set email alerts
|

Steep increase in HIV prevalence among tuberculosis patients in Ho Chi Minh City

Abstract: In Vietnam the spread of HIV infection is thought to be limited. In 12 urban districts of Ho Chi Minh City representative samples of tuberculosis patients have undergone HIV testing since 1995. HIV prevalence increased steeply from 0.5% in 1995 to 4% in 2000, with a doubling time of approximately 21 months. This study highlights the need to intensify HIV/AIDS prevention and control in Vietnam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 3 publications
1
11
0
Order By: Relevance
“…We found the lowest MDR rate in the age group of 15 -24 years. Similarly, in the previous studies the lowest MDR rate was reported in the younger age groups (in the 10 -19 and 15 -24 age groups) [13] [14]. Presumably, the reason of the low MDR rate in the younger age is the more new TB cases in this age group.…”
Section: Age (Years) Mdr + N (%) Mdr − N (%) Totalsupporting
confidence: 69%
See 2 more Smart Citations
“…We found the lowest MDR rate in the age group of 15 -24 years. Similarly, in the previous studies the lowest MDR rate was reported in the younger age groups (in the 10 -19 and 15 -24 age groups) [13] [14]. Presumably, the reason of the low MDR rate in the younger age is the more new TB cases in this age group.…”
Section: Age (Years) Mdr + N (%) Mdr − N (%) Totalsupporting
confidence: 69%
“…Another factor is higher number of males than females with tuberculosis. However, some studies reported no difference for the rate of MDR TB with respect to gender [13] [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In more recent years, however, rising HIV infection rates in TB patients have been documented in Ho Chi Minh City, the major urban area with the highest HIV prevalence in the country ( 11 ). Since 1997, Ho Chi Minh City has also reported increasing TB rates, particularly for young adults ( 12 ).…”
mentioning
confidence: 99%
“…However, rifampin resistance can be used as a surrogate marker of MDR-TB in many settings (21,26 (17). Around 25% of primary isolates are isoniazid resistant in Ho Chi Minh City, and 15% are isoniazid and streptomycin dual resistant (15).…”
mentioning
confidence: 99%